Wettability effect of PECVD-SiOx films on poly(lactic acid) induced by oxygen plasma on protein adsorption and cell attachment - Sarapirom S. (2014)
Surface wettability is an important property of biomaterials. Silicon oxide films have a wide range of applications due to a range of the properties such as the mechanical strength and surface wettability. This paper reports effect of the surface wettability of silicon oxide (SiOx) films on protein adsorption and cell attachment and proliferation. SiOx films were deposited onto poly(lactic acid) (PLA) substrate using plasma enhanced chemical vapor deposition (PECVD). Octamethylcyclotetrasiloxane (OMCTS:Si 4O4C8H24) was used as a precursor with O2 as a carrier gas. After deposition, the films were treated with O2-plasma to adapt wettability. It was found that O 2-plasma enhanced the wettability of the films without changing the film thickness, while made the surface morphology slightly smoother. The polar component increased after O2-plasma treatment as observed in the contact angle measurements. The surface energy of the films was calculated by means of the Owens-Wendt method to resolve the contributions of polar and dispersive components. The chemical structure was characterized using attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy. The films were dense with a high Si-network structure. The reduced carbon content (-CHn, Si-CH3) and increased hydrogen content (-OH) of the O2-plasma treated SiOx films led to the polar components enhancing the SiOx wettability. Adsorption of bovine serum albumin (BSA) on the films was investigated by using x-ray photoelectron spectroscopy (XPS). More BSA was adsorbed onto the O2-plasma treated SiO x films. Attachment and proliferation of MC3T3-E1 mouse pre-osteoblasts and L929 mouse fibroblasts cells on the SiOx films were evaluated via MTT assay. The cells were attached more to the untreated SiOx films but proliferated more on the surface of the O 2-plasma treated SiOx films depending on the cell types. © IOP Publishing Ltd 2013.